THE IMPLEMENTATION OF CLOCK AS MEDIA IN TEACHING GRAMMAR - - - Yuliarsih; Fetty . Nuritasari (Universitas Madura, 2019)
Grammar means a lesson about principles on creating and clustering words into sentences. So that, grammar is very important for people who wants conquering words in English well, because it can guide us to cluster words and sentences correctly. As EFL students almost most of them difficult to mastery English grammar, they found it difficult when they have to use it in their practices. The most difficult part is the verb changing is rather annoying to use. This research aim’s to investigate the implementation of clock as media in teaching grammar in Madura University. It employs a qualitative design. The data of the research were collected through observation, interview and documentation with the descriptive approach. This study focuses on how the clock is applied as a learning media on changes of verbs form, especially irregular verbs. This research was conducted in English Education department of Madura University. Research subjects are students who take Structure class academic Year 2018/2019 Class A. From the data there are 53.3% of students give positive respond toward the implementations of clock as media in teaching grammar especially in changes of verb form. It help them to memorize the irregular verbs.